COMmunication with Families regarding ORgan and Tissue donation after death in intensive care (COMFORT): protocol for an intervention study. Issue 1 (December 2017) - Potter, Julie; Herkes, Robert; Perry, Lin; Elliott, Rosalind; Aneman, Anders; Brieva, Jorge; Cavazzoni, Elena; Cheng, Andrew; O'Leary, Michael; Seppelt, Ian; Gebski, Val
Abstract Background Discussing deceased organ donation can be difficult not only for families but for health professionals who initiate and manage the conversations. It is well recognised that the methods of communication and communication skills of health professionals are key influences on decisions made by families regarding organ donation. Methods This multicentre study is being performed in nine intensive care units with follow-up conducted by the Organ and Tissue Donation Service in New South Wales (NSW) Australia. The control condition is pre-intervention usual practice for at least six months before each site implements the intervention. The COMFORT intervention consists of six elements: family conversations regarding offers for organ donation to be led by a "designated requester"; family offers for donation are deferred to the designated requester; the offer of donation is separated from the end-of-life discussion that death is inevitable; it takes place within a structured family donation conversation using a "balanced" approach. Designated requesters may be intensivists, critical care nurses or social workers prepared by attending the three-day national "Family Donation Conversation" workshops, and the half-day NSW Simulation Program. The design is pre-post intervention to compare rates of family consent for organ donation six months before and under the intervention. Each ICU crosses from using the control to intervention condition after the site initiation visit. The primary endpoint is the consent rate for deceased organ donation calculated from 140 eligible next of kin families. Secondary endpoints are health professionals' adherence rates to core elements of the intervention; identification of predictors of family donation decision; and the proportion of families who regret their final donation decision at 90 days. Discussion The pragmatic design of this study may identify 'what works' in usual clinical settings when requesting organ donation in critical care areas, both in terms of changes in practice healthcare professionals are willing and able to adopt, and the effect this may have on desired outcomes. The findings of this study will be indicative of the potential benefits of the intervention and be relevant and transferrable to clinical settings in other states and countries. Trial registration Australian New Zealand Clinical Trials Registry (ANZCTR):ACTRN12613000815763 (24 July 2013). ClinicalTrials.gov:NCT01922310 (14 August 2013) (retrospectively registered).